PP.42.06: FOKI AND BSMI VITAMIN D RECEPTOR GENE POLYMORPHISMS, PLASMA RENIN ACTIVITY AND ESSENTIAL ARTERIAL HYPERTENSION. (June 2015) - Guglielmo, C.; Cottone, S.; Guarino, L.; Arsena, R.; Scazzone, C.; Tornese, F.; Guarneri, M.; Bono, A.; Mulé, G.
Abstract : Objective: Our aims were to analyze the relationship between 25-hydroxyvitamin D (25[OH]D) plasma levels and clinical and ambulatory blood pressure (BP) values, and to identify any possible association between hypertension and FokI and BsmI vitamin D receptor (VDR) gene polymorphisms in essential hypertensive patients. Design and method: Seventy-one essential hypertensive patients and seventy-two controls, 18–75 years old, were enrolled. Clinical physical examination, routine blood chemistry, clinical BP, 24 hour ambulatory blood pressure monitoring, 25[OH]D and Plasma Renin Activity (PRA) assay, and FokI and BsmI VDR polymorphisms analysis were obtained. Results: We observed a significant negative correlation between 25[OH]D and 24 h systolic BP (r = -0.277, p = 0.043) (Figure 1). Figure. No caption available. This correlation persisted in backward stepwise multivariate analyses (β=-0.337; p = 0.022) including as covariates first age, gender, body mass index, glomerular filtration rate estimated (eGFR) by MDRD equation, and secondly PRA. Furthermore body mass index (β=0.290; p = 0.037) and eGFR-MDRD (β=-0.301; p = 0.038) were independently correlated to 24 h systolic BP. We did not observe statistically significant correlation between 25[OH]D and PRA. When we compared anthropometric, clinical and bio-humoral parameters among patients with different VDR (FokI and BsmI) genotypes, we found a significant difference of clinic diastolic BP values among the three FokI genotypes (p = 0.018). Significantly higher diastolic BP values in patients with ff FokI genotype compared with patients with Ff FokI genotype (p = 0.002) were disclosed through the Mann-Whitney U test. Lastly any association between a specific genotype or allele and hypertension or PRA was not found when we compared allelic frequencies and genotype distribution between patients and controls. Conclusions: Our findings confirm the relation between 25[OH]D and BP values in essential hypertensive patients and they suggest that FokI and BmsI VDR polymorphisms is not associated either with hypertension or with PRA.